From "Organizational Behavior" to "Organizational Misbehavior": Toward New Perspectives in Teaching People Management (GESTIÓN Y TENDENCIAS, 2024)
This note seeks to highlight the need to orient teaching in the field of "People Management" toward theoretical perspectives drawn from the sociology of work and from labor process theory, so that students may reflect on the characteristics of the capitalist socioeconomic context —that is, the context of market economies— within which the behavior of people in organizations is framed. In this sense, it may be regarded as a contribution toward a critical approach to the field's study and teaching, which today is very strongly tied to perspectives rooted in behavioral psychology and centered on a selection of success stories from United States companies.
Keywords: people management; human resource management; sociology of work